2021
DOI: 10.1016/j.arrct.2021.100136
|View full text |Cite
|
Sign up to set email alerts
|

Electromyography Recordings Detect Muscle Activity Before Observable Contractions in Acute Stroke Care

Abstract: Objective To evaluate muscle activity in the arms of adult stroke survivors with limited or no arm movement during acute care. Design Prospective observational study. Setting Acute care regional stroke center. Participants We recruited adults (N=21) who had a stroke within the previous 5 days who were admitted to a level 1 trauma hospital and had a National Institutes of Health Stroke Scale score >1 for arm functio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Our results reflected the difficulty of muscle activation in patients with a higher level of upper limb motor impairment. Papazian et al affirmed that in severely impaired patients, there were upper limb muscle contractions without visible movements, but they reflected random and uncontrolled muscle activity [ 29 ]. However, sEMG-driven interventions should be feasible to this type of patient when considering the limited rehabilitation options available for people with severe upper limb impairments [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results reflected the difficulty of muscle activation in patients with a higher level of upper limb motor impairment. Papazian et al affirmed that in severely impaired patients, there were upper limb muscle contractions without visible movements, but they reflected random and uncontrolled muscle activity [ 29 ]. However, sEMG-driven interventions should be feasible to this type of patient when considering the limited rehabilitation options available for people with severe upper limb impairments [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Papazian et al affirmed that in severely impaired patients, there were upper limb muscle contractions without visible movements, but they reflected random and uncontrolled muscle activity [ 29 ]. However, sEMG-driven interventions should be feasible to this type of patient when considering the limited rehabilitation options available for people with severe upper limb impairments [ 29 ]. These data suggested that more investigation of sEMG-driven intervention of patients with severe motor impairment is needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Electromyography can quantitatively and qualitatively analyze the neuromuscular function of target muscles by collecting surface signals during muscle activity and speculating on the damage extent and nature of target muscles, thereby offering noninvasive and real-time measurements ( Cè et al, 2020 ; Feldner et al, 2021 ; Fujita et al, 2021 ; Papazian et al, 2021 ). Liu et al (2022) combined sEMG devices and video games to develop a biofeedback-based therapeutic play system, which could improve patient training initiative and compliance.…”
Section: Discussionmentioning
confidence: 99%